Operational and Externality Risk Management on Cooperative Performance: Moderating Role of Good Governance in Indonesia - Sulistyaningsih, Dwi Juwita; Lindrianasari (Institut Bisnis dan Informatika Kesatuan, 2025)
Cooperatives face performance challenges influenced by operational and external risks, thereby necessitating effective risk management and the application of good governance to strengthen resilience, competitiveness, and long-term sustainability. This study examined how operational and externality risk management affect Indonesian cooperative performance, with excellent governance as a moderator. To quantify variable interactions more precisely, the research used a quantitative method with an associative approach. Two hundred managers and cooperative administrators from Indonesian areas participated in the study. These individuals were chosen based on their roles because they directly influence decision-making and how their cooperatives manage risks and governance. Partial Least Squares (PLS) with SmartPLS 3.0 software was used to analyze complex models and examine moderating effects. Findings highlighted numerous key insights. First, cooperative performance improved greatly with operational risk management. To run more efficiently, cooperatives must anticipate system, human resource, and process failures. Second, externality risk management improved cooperative performance significantly, emphasizing the need for cooperatives to anticipate market, policy, and social changes that may threaten their stability. Most importantly, excellent governance improves these connections by encouraging transparency, accountability, and fairness, boosting risk management benefits. These findings show that risk management and good governance help Indonesian cooperatives succeed.